Using possihilities of sugar heet pulp silage prcduced in different ways in lamb and dairy cut diets iv. milk composition, some blood and rumen fluid parameters - Suphi Deniz; Şakir D. Tuncer; Murat Demirel; Nihat Denek (Eurasian Journal of Veterinary Sciences)
The objectives ol this experimenIs were to evaluate the ensiling melhods for possibly more ellicıent and longlastıng erese-venon of sugar beet polp, rich in energy and cheap leedstuff. For this reason, silages dry matter increased to 20% by adding wheat straw or grass hayand added 5% beet molasses, and 1% urea in only wheat straw con taining sılage. These twosilages and com silage and grass hay were Ulilized in dairy cow diets. In daiıy cow trial , DM intake of daiıy cow were sinnla ramong silages, but higher in dairy cow led grass hay compared with those fed silage diets (P<0.05). Total milk, tat corrected mrlk, solid correcıed milk prcd uctlons and cornposıtıon of milk we re similar among oets. Rumen pH were similar, nowever, rumarı NH3-N ccncentrations were higher in cows led SBPSM silage wilh cows Ied grass hay 3-h pos treeding (P<0.05). While leetıc acid and prc pionic acid concentrations of rumen fluid we re similar, bui ecetcacid concentratrens ol cows led SBPHM silage were ıower lh an those cows fed other dıe ts (P<0.05). Whereas lotal serum oroteo. glueose. calcium, and lriglyeeride corıce n lra tıon s were similar, serum urea-N, phosphorous and cholesterol concenlralions were different among treatment groups (P<0.05). In conclusion, when DM corıcentralion ol sugar bee t pulp ineteased up to 20% and suppJemenled with moıasses, a salisfying quaıey silage can be accomplished. The nutnnve value ol th ıs silage may equal LOthe nutritive value ol com silage. Results obtained in dairy cow experiment were verv enceuraging, the use of sugar beet pulp silage.